PERBANDINGAN UJI RESISTENSI BAKTERI STAPHYLOCOCCUS AUREUS TERHADAP OBAT ANTIBIOTIK AMPISILIN DAN TETRASIKLIN - Finnie Luthfia Suheri; Zulkarnain Agus; Ivony Fitria (Andalas Dental Journal, 2015)
Staphylococcus aureus is one of the normal flora in the oral cavity, but these bacteria can change to be pathogen if there are predisposing factors such as changes in quantities of bacteria and decreasing of the immune response of the body. One of the ways to prevent is to inhibit the activity of these bacteria using antibiotics. Ampicillin and tetracycline are the broad-spectrum antibiotics that can inhibit the growth of positive and negative gram bacteria. This research was a laboratory experimental with Kirby-Bauer method and using CLSI standard. Total sample are 16 discs of ampicillin and 16 discs of tetracycline then placed on MHA media contain Staphylococcus aureus to see the inhibition power. The result showed that the averages of inhibition zone of ampicillin is 36,64 mm while tetracycline is 25,58 mm. Independent sample t- test showed that p<0,01 which means there is a significantly difference between ampicillin and tetracycline. Ampicillin and tetracycline can inhibit the growth of Staphylococcus aureus with sensitive categories. Ampicillin is more sensitive and effective than tetracycline to inhibit the growth of Staphylococcus aureus